Classifications and Properties of Materials for Chairside Computer-Aided Design/Computer-Aided Manufacturing Dentistry: A Review - S Eskandarion; M Neshandar; R Rokhshad (Islamic Azad University, 2021)
Background and Aim: Chairside computer-aided design/computer-aided manufacturing (CAD/CAM) systems have become considerably more accurate, reliable, efficient, fast, and prevalent since 1985 when CEREC was introduced. The inceptive restorative material option for chairside CAD/CAM restorations was limited to ceramic blocks. Today, restorative material options have been multiplied and include metal alloys, ceramics, oxide ceramics, resins, and resin-matrix ceramics (RMC). This study aimed at making an overview of chairside CAD/CAM system materials and classifications. Materials and Methods: An electronic search of the literature was carried out mainly through PubMed, ScienceDirect, Cochrane Library, and Google databases. The search aimed at collecting all the relevant English articles from 1965 to 2020. Results: The analysis of the bond strength, fatigue resistance, flexural strength, elastic constants, microstructural characterization, accuracy, and clinical success of the materials showed variable outcomes. The marginal adaptation of resin ceramics has been reported to be comparable to that of lithium disilicate. It has been reported that the chairside CAD/CAM system using intraoral scanning is at least as accurate as the conventional method. Conclusion: Chairside CAD/CAM restorations are fast, reliable, predictable, effective, patient-friendly, and cost-effective treatment options. Design software and intraoral scanners have made the treatment procedure simple. Chairside individualization of dental restorations could help improve patient satisfaction. However, considering the limited long-term clinical data, future studies need to address the long-term clinical performance of chairside CAD/CAM materials.